Activation of Au-CeO2 composites prepared by pulsed laser ablation in the reaction of low-temperature CO oxidation - Stadnichenko, Andrey I.; Slavinskaya, Elena M.; Fedorova, Elizaveta A.; Goncharova, Darya A.; Zaikovskii, Vladimir I.; Kardash, Tatyana Yu; Svetlichnyi, Valerii A.; Boronin, Andrei I. (Journal of structural chemistry)
The Au/CeO2 composite catalyst is prepared by pulsed laser ablation in liquid (PLAL). Dispersions of gold and cerium are prepared in alcohol and water, respectively, mixed, dried, and annealed at various temperatures: 450 °C, 600 °C, 800 °C. It is shown by a number of physical methods (XPS, XRD, HRTEM, Raman spectroscopy) that a contact interaction between gold and cerium oxide particles is formed as a result of annealing in air or upon exposure to a reaction medium. The XPS data indicate that, along with metal particles, there is an ionic gold state with Eb(Au4f7/2) = 85.3 eV. According to the Raman spectroscopy data (λ = 785 nm), CeO2 nanoparticles are highly defective and that gold clusters are stabilized on vacancies in the cerium oxide lattice. Catalytic tests in the CO+O2 reaction show that annealing at 450-600 °C in air or in the reaction medium activates the catalysts and initiates intense lowtemperature activity. The calculated values of the active site turnover frequency (TOF) are 0.08 s-1 at 0 °C and 0.17 s-1 at 20 °C. According to the XRD and XPS data, annealing the sample at 800°C leads to its complete reduction and to the sintering of gold into large particles resulting in a loss of low-temperature activity